Acute Myelitis, Recurrent Optic Neuritis, and Seizures Over 17 Years - Zhao, Chen; Li, Aijun; Liu, Lei; Wang, Jiawei; Fan, Dongsheng (Frontiers in Neurology, 2020)
Recent discovery of several autoantibodies, such as aquaporin-4 immunoglobulin G antibodies (AQP4-IgG), myelin oligodendrocyte glycoprotein immunoglobulin G antibodies (MOG-IgG) and glial fibrillary acidic protein immunoglobulin G antibodies (GFAP-IgG), has greatly facilitated differential diagnosis of autoimmune disorders of the central nervous system. Here we report an interesting case with a history as long as 17 years. Only until she was tested positive for MOG-IgG that her diagnosis was revised from multiple sclerosis to MOG-associated disease (MOGAD). Our case illustrates the significance of screening autoantibodies in patients suspected of inflammatory autoimmune neurologic disorders. In addition, this case demonstrates how MOGAD manifests and develops in a patient over a decade.